Peran Anggaran dalam Mengambil Keputusan Manajerial di Perusahaan - Muammar Khaddafi; Fuja Mastiara; Nadia Agustina; Hidayanti Hidayanti; Halimah Halimah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The budget is an important tool in the managerial decision making process. As a structured financial guide, budgets help managers plan, coordinate and control company resources. Through budget preparation, managers can determine cost requirements, allocate resources effectively, and set financial targets that support the achievement of organizational goals. Additionally, budgets serve as performance evaluation tools, allowing managers to compare actual results with projections, identify deviations, and take necessary corrective actions. Using the right budget also helps management reduce health risks, increase operational efficiency, and ensure that strategic decisions are based on measurable and accountable information. Thus, the budget plays a crucial role in supporting a more rational and focused decision-making process.